Neurodidactic Teaching and Learning Strategies for Legal Research (Docentes 2.0 Journal, 2021)
The fact that each brain is unique and points to the need to consider the diversity of students and the fact that teachers are flexible in training and evaluation processes. If all students can improve, teachers' expectations towards them must always be positive, applying strategies that develop the emotional-affective, combining with the rational, where they do not have to condition negative attitudes or past behaviors. Emotions are unconscious reactions that nature has devised to ensure survival that, for our benefit, we must learn to manage, not eradicate. Neuroscience has shown that emotions maintain curiosity; they serve both to establish communication, being essential in reasoning processes, as, in decision-making, emotional and cognitive processes are inseparable. The objective of the research was to identify neurodidactic strategies for the teaching-learning process of Legal Research in the last semesters of the Law Degree; Through Participatory Action Research applying the participant-observation method with a first strategic academic tool of diagnostic evaluation commanded by the neurodidactic way using the descriptive, developing criteria for consideration in this article that result in the following results: Student-centered methodologies, meaningful learning, linking theory with practice, and recognition of the emotional are some of the neurodidactic strategies identified.
Keywords: Neurodidactic; strategies; methodologies; emotional education; meaningful learning